Mechanical and dielectric characterization of hemp fibre reinforced polypropylene (HFRPP) by dry impregnation process (eXPRESS Polymer Letters, 2010)
Natural fibres such as jute, coir, sisal, bamboo and pineapple are known to have high specific strength and can be effectively used in composites in various applications. The use of hemp fibres to reinforce the polymer aroused great interest and expectations amongst scientists and materials engineers. In this paper, composites with isotactic polypropylene (iPP) matrix and hemp fibres were studied. These materials were manufactured via the patented FIBROLINE process based on the principle of the dry impregnation of a fibre assembly with a thermoplastic powder (iPP), using an alternating electric field. The aim of this paper is to show the influence of fibre/matrix interfaces on dielectric properties coupled with mechanical behaviours. Fibres or more probably the fibre/matrix interfaces allow the diffusion of electric charges and delocalise the polarisation energy. In this way, damages are limited during mechanical loading and the mechanical properties of the composites increase. The structure of composite samples was investigated by X-ray and FTIR analysis. The mechanical properties were analysed by quasistatic and dynamic tests. The dielectric investigations were carried out using the SEMME (Scanning Electron Microscope Mirror Effect) method coupled with the measurement of the induced current (ICM).